Correction: H2 as a fuel for flavin- and H2O2-dependent biocatalytic reactions. Issue 66 (4th August 2020) - Al-Shameri, Ammar; Willot, Sébastien J.-P.; Paul, Caroline E.; Hollmann, Frank; Lauterbach, Lars
Abstract : Correction for 'H2 as a fuel for flavin- and H2 O2 -dependent biocatalytic reactions' by Ammar Al-Shameri et al., Chem. Commun., 2020, DOI: ; 10.1039/d0cc03229h .